PENDAMPINGAN DAN UJI KOMPETENSI KEAHLIAN SMK ISLAM AL BAROKAH - Muhamad Muslihudin; Mardiyanto Mardiyanto; Siti Mukodimah (LP3K Lampung, 2023)
Assistance and skills competency tests in SMK are important aspects in ensuring the quality of education provided to students. Assistance is carried out to assist students in developing the skills and knowledge needed to meet established competency standards. Meanwhile, the skills competency test aims to evaluate students' ability to apply the knowledge and skills they have learned while at SMK. This study aims to explore and understand mentoring and skills competency testing in SMK, with a focus on the roles and benefits of these two aspects. Data was collected through interviews with teachers and students in SMKs that have mentoring programs and skills competency tests. The results of the study show that mentoring and expertise competency tests have an important role in helping students prepare themselves to enter the world of work or continue their education to a higher level. Mentoring can assist students in developing skills that cannot be learned through theoretical learning alone, while skills competency tests can ensure that students have met the competency standards needed for success in the future.